KESIAPAN GURU DALAM MENGHADAPI PEMBELAJARAN TATAP MUKA - Anies listyowati; Titah Kinasih; Andri Kurniawan (Kanigara, 2022)
The pandemic situation that has gradually improved has an impact on the learning process that is carried out offline (outside the network) while still paying attention to the conditions for the implementation of safe learning. As parents and educators, we must begin to prepare psychologically for children. The current situation has gradually returned to normal, so that the teaching and learning process can be carried out optimally, especially for early childhood whose learning must be carried out in a fun way, namely playing while learning, between children and teachers must meet each other directly so that children can experience fun learning. School institutions and teachers are obliged to prepare both infrastructure and mental facilities and no less important is the flow of how to organize learning in accordance with technical guidelines from the government so that learning can take place safely and smoothly. Therefore, high synergy is needed between school institutions, parents and the government. With this service program, it is hoped that the PGPAUD Study Program at PGRI Adi Buana University Surabaya will be able to take part in helping teachers in preparing matters related to face-to-face learning.